Detection and quantification of Mycobacterium tuberculosis antigen CFP10 in serum and urine for the rapid diagnosis of active tuberculosis disease - Marva Seifert (Scientific Reports, 2021)
Abstract Outside of the ongoing COVID-19 pandemic, tuberculosis is the leading cause of infectious disease mortality globally. Currently, there is no commercially available point-of-care diagnostic that is rapid, inexpensive, and highly sensitive for the diagnosis of active tuberculosis disease. Here we describe the development and optimization of a novel, highly sensitive prototype bioelectronic tuberculosis antigen (BETA) assay to detect tuberculosis-specific antigen, CFP10, in small-volume serum and urine samples. In this proof-of-concept study we evaluated the performance of the BETA assay using clinical specimens collected from presumptive tuberculosis patients from three independent cohorts. Circulating CFP10 antigen was detected in ALL serum (n = 19) and urine (n = 3) samples from bacteriologically confirmed tuberculosis patients who were untreated or had less than one week of treatment at time of serum collection, successfully identifying all culture positive tuberculosis patients. No CFP10 antigen was detected in serum (n = 7) or urine (n = 6) samples from individuals who were determined to be negative for tuberculosis disease. Additionally, antigen quantification using the BETA assay of paired serum samples collected from tuberculosis patients (n = 8) both before and after treatment initiation, indicate consistently declining within-person levels of CFP10 antigen during treatment. This novel, low-cost assay demonstrates potential as a rapid, non-sputum-based, point-of-care tool for the diagnosis of tuberculosis disease.